Climate Change Education Based on Indigenous Knowledge: Fostering Disaster Literacy in Social Studies Learning - Kirana Prama Dewi; Esti Sarjanti; Anissa Rahma Fanilika; Destri Ratna Ma'rifah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Climate change is a significant threat to human existence in the 21st century, necessitating the integration of climate change education into the social studies curriculum to equip students with environmental awareness and disaster literacy. This research aims to describe the implementation of climate change strategy materials grounded in Indigenous Knowledge (IK) and to determine students' disaster literacy levels through the StudySaster learning model. Studysaster is a systematic learning paradigm that integrates disaster education into the school environment across the pre-disaster, emergency response, and post-disaster phases. This study uses an exploratory sequential mixed-methods design with a sample of 121 elementary school teacher students at Universitas Ahmad Dahlan, Yogyakarta. Data were collected through observations, interviews, and questionnaires adapted from the disaster literacy framework by Kimura et al. to measure the dimensions of knowledge, attitudes, and skills. The research results show that: 1) the implementation of the Studysaster method reached a convenient category with an average score of 4.5/5.0; 2) the use of interactive learning media SWAY based on Indigenous Knowledge effectively enhances students' disaster literacy; and 3) the students' disaster literacy profile is in the high category, with the highest achievements in the attitude aspect (75% for respect toward the environment) and knowledge (50% for information understanding), while the skills dimension is the weakest competency aspect. These findings imply the importance of making disaster literacy a daily practice and provide a reference for social studies educators in integrating disaster mitigation into classroom learning.